130k views
4 votes
17........................

17........................-example-1
User Heli Shah
by
5.5k points

2 Answers

3 votes

Answer:

Explanation:

First, add 3 to both sides:

-5 = -6∛(x²)

Next, divide both sides by -6, to isolate ∛(x²):

5/6 = ∛(x²)

Eliminate the radical by cubing both sides:

---- = x²

Finally, take the square root of both sides. This will isolate x. There will be two roots: one +, the other -.

x = ±√(5³/6³)

This simplifies to: ± (5/6)∛(5/6).

User Javydreamercsw
by
5.8k points
5 votes

Answer:

a.
0.76,-0.76

Explanation:

The given equation is;


-8=-3-6\sqrt[3]{x^2}

Add 3 to both sides of the equation to get;


-8+3=-3+3-6\sqrt[3]{x^2}


\Rightarrow -5=-6\sqrt[3]{x^2}

Divide both sides by -6.


\Rightarrow (-5)/(-6)=\sqrt[3]{x^2}


\Rightarrow (5)/(6)=\sqrt[3]{x^2}

Cube both sides of the equation;


\Rightarrow ((5)/(6))^3=x^2


\Rightarrow (125)/(216)=x^2

Take square root of both sides


\pm \sqrt{(125)/(216)}=x


\pm 0.76=x


\therefore x=0.76,-0.76

User Jbernadas
by
5.8k points